Branches of Trigeminal Nerve Causing Idiopathic Trigeminal Neuralgia and Effectiveness of Microvascular Decompression for Immediate Pain Relief - Shah, Inayat; Khan, Hameed Ullah; Wardag, Ghulam Mustafa; Shah, Aimen Mahmood; Shah, Syed Gulrukh Saba; Khan, Jamal Nasir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the efficacy of microvascular decompression for immediate pain relief of idiopathic trigeminal, caused by different branches of trigeminal nerve. Study Design: Descriptive study. Place and Duration of Study: Department of Neurosurgery, Mardan Medical Complex, Mardan from 1st January 2020 to 30th June 2021. Methodology: One hundred and thirty nine patients were collected from Tertiary Care Hospitals of KPK. A consent form and detailed history was performed with clinical examination and relevant investigations like CT and MRI of the brain. Pre-operative preparation was done with following investigations like complete blood count and viral serology for hepatitis, coagulation profile was carried out. Patients was assessed and included in the study according to the inclusion and exclusion criteria. The patients were operated by the same neurosurgeon. Patients were assessed after 72 hours post-operatively for pain relief by Visual Analogue Scale (VAS- Scale). Results: The mean age was 63±12.24 years. The data was divided into two 37% male and 63% females were included in the study. The most common branch of trigeminal nerve causing pain is right infraorbital (V2), (45) 32.37% and 23.02% is right inferior alveolar nerve V3. The less common branch of mandibular nerve is right lingual nerve 0.719 %. The study showed that microvascular decompression was effective in 88% patients and was not effective in 12% patients. The trigeminal neuralgia is common in old age patients from 60 to 80 years that is 45%. Conclusion: The most common branch of the trigeminal nerve was right infraorbital nerve causing pain in old age individuals and it is concluded that microvascular decompression was 88% effective in idiopathic trigeminal neuralgia in terms of immediate pain relief.